The Growth and Yield of Sweet Corn under Minimum Tillage Technology by Using Various Doses of Herbicide Mixtures of Glyphosate and 2,4-D - Simanuhuruk, Bilman Wilman; Simarmata, Marulak; Aprianto, Ayyi (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2019)
Glyphosate is a widely used herbicide for minimum tillage technology because it effectively kills broadleaf and grass weeds. Mixing glyphosate with other herbicide that has a different mechanism, such as 2,4-D may increase control efficacy and prevent the evolved of resistant weeds. Research was conducted to obtain the effective dose of glyphosate and 2,4-D mixtures and to evaluate the effect of the herbicide mixtures on the growth rate and yield of sweet corn. Depression on summed dominance ratios (SDR) and increased number of dominant weeds were observed after the application of glyphosate and 2,4-d mixtures. The interaction of the herbicide mixtures was observed optimum at the doses of glyphosate and 2,4-D of 1.94 and 1.5 L ha-1, respectively, with maximum of net assimilation rates (NAR) at 4-6 weeks after planting of 0.0003617 g cm-2 days-1. Plant growth rates (PGR) and NAR were observed maximum by a single treatment of glyphosate at a dose of 1.5 L ha-1 which were 2.23614 and 2.23607813 g cm-2 days-1, respectively. Yield of sweet corn observed as fresh-weight of cobs was found maximum of 129.41 g with a single treatment of glyphosate at 2,018 L ha-1.